Where to look for the morals in markets? - Matthias Sutter; Jürgen Huber; Michael Kirchler; Matthias Stefan; Markus Walzl (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2018)
There is a heated debate on whether markets erode social responsibility and moral behavior. However, it is a challenging task to identify and measure moral behavior in markets. Based on a theoretical model, we examine in an experiment the relation between trading volume, prices and moral behavior by setting up markets that either impose a negative externality on third parties or not. We find that moral behavior reveals itself in lower trading volume in markets with an externality, and in prices depending on the market structure. We further investigate individual characteristics that explain trading behavior in markets with externalities.
Keywords: C92; D03; D62; 330; Morals; Markets; Competition; Experiment